2017
DOI: 10.1186/s12888-017-1449-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic distribution of the total and individual item scores on the Kessler Screening Scale for Psychological Distress (K6) in US adults

Abstract: Background: The distributional pattern of total scores on depression screening scales in the general population has not been well studied. Recent studies suggest that the total scores on depression screening scales follow an exponential pattern, with the exception of the lower end of the distribution. To further investigate the findings, we determined the distributions of the total and individual item scores on the Kessler Screening Scale for Psychological Distress (K6). Methods: Data were obtained from the Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
(46 reference statements)
3
18
1
Order By: Relevance
“…In contrast, the total scores with a low probability for the negative adverb option exhibited lower scores. Indeed, according to our calculations, the average probabilities of “none of the time” for 1997 and 2017 (74.1% and 74.0%, respectively) were higher than that of the National Survey of Midlife Development in the United States data (61.8%), which exhibited an exponential pattern for the whole distribution 41 . Our recent simulation using an ordinal scale model revealed that when the severity of psychological distress followed an exponential distribution, the total scores of a psychological distress scale exhibited an exponential pattern, except at the lower end of the distribution 42 .…”
Section: Discussioncontrasting
confidence: 62%
“…In contrast, the total scores with a low probability for the negative adverb option exhibited lower scores. Indeed, according to our calculations, the average probabilities of “none of the time” for 1997 and 2017 (74.1% and 74.0%, respectively) were higher than that of the National Survey of Midlife Development in the United States data (61.8%), which exhibited an exponential pattern for the whole distribution 41 . Our recent simulation using an ordinal scale model revealed that when the severity of psychological distress followed an exponential distribution, the total scores of a psychological distress scale exhibited an exponential pattern, except at the lower end of the distribution 42 .…”
Section: Discussioncontrasting
confidence: 62%
“…These findings are consistent with results of other nationally representative surveys that the K6, CIS-R, and CES-D in the USA, England, and Japan, respectively [ 15 , 17 , 18 ]. Previous research demonstrated that the response rate of the negative adverb option (“not at all”) plays an important role in predicting the non-exponential pattern at the lower end of the distribution [ 13 , 33 ]. Specifically, at the lower end of the distribution, the sum of the item scores with a high rate for the negative adverb option showed higher scores in comparison with those expected from the exponential pattern.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is no evidence that the latent variable of depressive symptom scores in the general population follows a normal distribution. Given that the pattern of item responses has repeatedly shown a non-normal distribution, the normal distribution model of depressive symptom scores could require reconsideration ( 27 ).…”
Section: Discussionmentioning
confidence: 99%